Effect of Temperature on Yield Product and Characteristics of Bio-oil From Pyrolysis of Spirulina platensis Residue - Siti Jamilatun; Yeni Elisthatiana; Siti Nurhalizatul Aini; Ilham Mufandi; Arief Budiman (Elkawnie, 2020)
Abstract : Dependence on the use of fossil fuels in Indonesia is still quite high, especially crude oil; if no new energy reserves found, it will disrupt long-term energy availability. Biofuel is a renewable energy source derived from biomass, such as the type of microalgae spirulina platensis (SP). Solid residues from SP extraction still contained high levels of protein and carbohydrates. This solid residue can be processed by pyrolysis to produce bio-oil, water phase, charcoal, and gas. Bio-oil and gas products can use as fuel, charcoal can use for pharmaceutical needs, and the water phase as a chemical can use in food and health. The pyrolysis process carried out in a fixed-bed reactor with temperature ranging from 300-600°C. Heating was carried out by electricity through a nickel wire wrapped outside the reactor. Pyrolysis product in the form of gas condensed in the condenser, the condensate formed measured by weight. Char weight measured after the pyrolysis process completed. At the same time, non-condensable gas calculated by gravity from the initial weight difference of SPR minus liquid weight (bio-oil and water phase) and char. SPR samples were analyzed proximate and ultimate, while bio-oil products examined by the GC-MS method. The experimental results showed that the optimum pyrolysis temperature at 500ºC produced by 18.45% of bio-oil, 20% of the water phase, 32.02 of charcoal, and 29.54% of gas by weight. GC-MS results from bio-oil consisted of ketones, aliphatics, nitrogen, alcohol, acids, while PAHs, phenols, and aromatics not found.Abstrak : Ketergantungan penggunaan bahan bakar fosil di Indonesia masih cukup tinggi terutama minyak mentah, jika tidak ditemukan cadangan energi baru maka akan mengganggu ketersediaan energi jangka panjang. Biofuel adalah salah satu sumber energi terbarukan yang berasal dari biomassa seperti jenis mikroalga spirulina platensis (SP). Residu padat dari ekstraksi SP masih mengandung protein dan karbohidrat yang cukup tinggi. Residu padat ini dapat diproses dengan pirolisis untuk menghasilkan bio-minyak, fase air, arang, dan gas. Produk bio-minyak dan gas dapat digunakan untuk bahan bakar, arang dapat digunakan untuk kebutuhan farmasi, dan fase air sebagai bahan kimia dapat digunakan di bidang makanan dan kesehatan. Proses pirolisis dilakukan dalam reaktor fixed-bed dengan suhu 300-600°C. Pemanasan dilakukan dengan listrik melalui kawat nikel yang dibungkus di luar reaktor. Produk pirolisis berupa gas dikondensasi dalam kondensor, kondensat yang terbentuk diukur beratnya. Berat char diukur setelah proses pirolisis selesai, sementara gas yang tidak dapat dikondensasi dihitung beratnya dari perbedaan bobot awal SPR dikurangi bobot cair (bio-oil dan fase air) dan char. Sampel SPR dianalisis proksimat dan ultimat, sedangkan produk bio-minyak dianalisis dengan metode GC-MS. Hasil percobaan menunjukkan bahwa suhu optimum pirolisis adalah 500ºC yang menghasilkan bio-oil, water phase, arang, dan gas berturut-turut adalah 18,45; 20;  32,02 dan 29,54 % berat. Hasil GC-MS dari bio-oil terdiri dari keton, alifatik, nitrogen, alkohol dan asam, sedangkan PAH, fenol dan tidak ditemukan.